The mediating effect of self-esteem on emerging adults’ materialism and anxiety - Rahmadina, Astri; Nashori, Fuad; Andrianto, Sonny (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
Anxiety disorders are defined by the World Health Organization (WHO) as the sixth most common non-lethal disease that contributes to a decline in global health. In emerging adulthood, which is the developmental stage of individuals aged 18-25, anxiety is the most common disorder. This study aims to determine the relationship between materialism and anxiety mediated by self-esteem in emerging adulthood in Yogyakarta, Indonesia. Data were collected through the quota sampling technique and involved 332 emerging adults aged 18-25, consisting of 69 men and 263 women. Measurements were made using the Materialistic Value Scale of Richins and Dawson, the Rosenberg Self-Esteem Scale, and the Beck Anxiety Inventory. The scales were distributed through an online questionnaire. Hypothesis testing was conducted using mediation regression analysis with the causal step method. The results show that all the regression paths were significant, indicating that self-esteem partially mediated the relationship between materialism and anxiety (B = 0.055, p < .01). The findings provide an overview of the dynamics of early adult individual anxiety related to materialism and self-esteem.